Konseling pada anak korban bencana alam: play therapy perspektif - Intan Sholihat; Deni Dzulfaqori Nasrullah (Seminar Nasional Bimbingan dan Konseling Jambore Konseling 3)
Natural disaster is surely effecting various disadvantages, such as the victims, properties, sorrows, and deep scared. For the victims who are in that condition is surely feeling afraid, worried, nervous, and easy to be panic. The victims of disaster can come and happen to adult and children. For traumatic solving to the children is really different from the solving traumatic to adult. The children have a susceptible condition to the impact that is caused by an event and make a traumatic impact. This research aims to solve a traumatic impact after the disaster to the children. By qualitative, this paper describes the case thoroughly. Through observing and giving treatment to the children who are the victims of natural disaster, found that those who gets traumatic can be cured. In such away that the play therapy are considered to solve that trauma.